1999
DOI: 10.1002/(sici)1099-0496(199905)27:5<336::aid-ppul7>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary echinococcosis (hydatidosis) in children: Results of surgical treatment

Abstract: From 1986–1996, 33 children with 49 pulmonary hydatid cysts underwent surgical treatment in Vienna and Istanbul. Cysts were unilateral in 28 and bilateral in 5 cases; unruptured cysts (URC) were diagnosed in 19 patients, and 14 children presented with ruptured cysts (RC). Ten patients had cysts in other organs (liver, spleen, central nervous system) in addition to pulmonary cysts. Diagnosis was primarily based on chest X‐ray and computed tomography scan. In Austrian children, a new combination of serological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 20 publications
2
24
0
4
Order By: Relevance
“…This technique is preferred by many clinics and is especially justified in children. 3,[9][10][11][12] Because the lung parenchyma has a great capacity for expansion, it is possible to leave a small area of parenchyma after the cyst is removed. We do not recommend enucleation and cystectomy because enucleation has a higher risk of contamination, and cystectomy increases the risk of air leaks and postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is preferred by many clinics and is especially justified in children. 3,[9][10][11][12] Because the lung parenchyma has a great capacity for expansion, it is possible to leave a small area of parenchyma after the cyst is removed. We do not recommend enucleation and cystectomy because enucleation has a higher risk of contamination, and cystectomy increases the risk of air leaks and postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…We performed cystotomy and capitonnage in 33 (94%) of the 35 patients in this series. Conservative surgery was performed in about 86.8% of 1596 patients, [1][2][3]10,12,14 but in only about 48.0% of another series of 245 patients because resection was preferred by the surgeons for all complicated and heavily infected cysts. 4,15,16 On the other hand, Kahraman et al 14 recently reported performing cystotomy and capitonnage for 40 of 42 (95.2%) patients with ruptured and complicated cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the delay in the diagnosis, the cyst were detected as larger sized cysts [7,13]. In our patient group, the cysts was 5 cm and bigger in diameter in 23 (69.7%) cases.…”
Section: Discussionmentioning
confidence: 63%
“…gana göre semptomlar ortaya çıkar. Bir yılda kistte 1 veya 2 cm çap artışı olabileceği bildirilmiştir (4,11,12) . Hidatik kistlerin çoğunun çocukluk çağında edinildiği fakat kistin yavaş büyüme özelliğinden dolayı 3.-4. dekadlara kadar tanı konulamadığı bildirilmektedir (12) .…”
Section: Gereç Ve Yöntemunclassified